A method for protecting and controlling access to JPEG2000 images - Serrão, C.; Serra, A.; Fonseca, P.; Dias, J. (Proceedings of SPIE - The International Society for Optical Engineering, 2003)
The image compression standard JPEG2000 brings not only powerful compression performance but also new functionality unavailable in previous standards (such as region of interest, scalability and random access to image data, through flexible code stream description of the image). ISO/IEC JTC1/SC29/WG1, which is the ISO Committee working group for JPEG2000 standardization is currently defining additional parts to the standard that will allow extended functionalities. One of these extensions is Part 8 JPSEC - JPEG2000 security, which deals with the protection and access control of JPEG2000 code-stream. This paper reports the JPSEC activities detailing with the three core experiments which are in progress to supply the JPEG2000 ISO Committee, with the appropriate protection technology. These core experiments are focusing on the protection of the code-stream itself and on the overall security infrastructure that is needed to manage the access rights of users and applications to that protected code-stream. Regarding the encryption/scrambling process, this one deals with the JPEG2000 code stream in such a way that only the packets, which contain image data information are encrypted. All the other code-stream data will be in clear mode. Ibis paper will also advance details of one of the JPSEC proposed solutions for the security infrastructure - OpenSDRM (Open and Secure Digital Rights Management) [16], which provides security and rights management from the content provider to the content final user. A use case where this security infrastructure was successfully used will also be provided.